Marijuana and E-Cigarette Adding New Challenges to Global Addiction Among Teenagers - Suhani Sanghai; Dr. Pratibha Mehetre (International Journal of Indian Psychȯlogy, 2022)
The study is focused on marijuana and e-cigarettes as the challenges in global addiction. Marijuana and e-cigarettes are one of the most frequently consumed substances in today’s generation. Addiction is nothing but dependency on something which cannot be controlled. As the generations are evolving we are exploring all aspects of the world and addiction is one of them. In the new generation addiction has become a huge part of our daily lives, addiction has many types, anyone can be addicted to anything. The present research is planned to study the new challenges adding to global addiction. To focus more on today’s generation, the researcher has planned to take the age group ranging from 10-12 to 18-20 years. The data of the research is focused more on teenagers and the objectives of the research are proven as the data has been gathered to get the result. The result shows that most of the teenagers think that marijuana and e-cigarettes are comparatively less risky than other substances and products, then next objective states that teenagers use marijuana and e-cigarettes because they face some psychological, physical and social issues and another objective states that media has a huge influence on teenagers regarding their perception towards marijuana and e-cigarettes.